HUBUNGAN FREKUENSI PENGGUNAAN APLIKASI PESAN ANTAR MAKANAN ONLINE DAN BESARAN UANG SAKU DENGAN KEJADIAN GIZI LEBIH PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN "VETERAN" JAKARTA - Navianur Prilia Putri (2023)
Based on Riskesdas data in 2018 stated that around 13,6% are overweight. In the current digital era, college students who are in the 19-24 year range take advantage of technology to access food more quickly, through an online food delivery application. However, the application displays more fast food. Excessive consumption of fast food can increase the incidence of overweight. In addition, socio-economic influences such as the amount of pocket money can be a factor of overweight. This study aims to determine the relationship between the frequency of using online food delivery applications and the amount of pocket money with the incidence of overweight in college students of the Faculty of Health Sciences UPN "Veteran" Jakarta. The research design used was cross-sectional with a sample of 136 respondents using a stratified random sampling technique. The results showed that there was no relationship between the frequency of using the online food delivery application and overweight (p = 0,676), there was no relationship between the amount of pocket money and overweight (p = 0,636), and there was a relationship between the amount of money pocket with the frequency of using online food delivery applications (p = 0,04). Based on these results, analyzing other factors that increase the risk of overweight in college students is still necessary.